Fluoride-modified TiO2 / COF photocatalyst and preparation method thereof

CN122912929APending Publication Date: 2026-10-16ORDOS INST OF APPLIED TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611384173.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]锐钛矿相二氧化钛(TiO2)由于具有非常好的化学稳定性、环保性、生物相容性以及经济实用性,已经在光催化方面得到了广泛的应用;该化合物具有3.0-3.2eV的宽禁带结构,但是由于它的固有的属性使其对于可见光的吸收效率很低,只能利用太阳辐射中紫外波段(占不到5%)的能量来进行光电转换,因此限制了光电转换效率的提高

Benefits of technology

本发明中,以二氧化钛纳米纤维作为内核,其具有的高比表面积可以提供出更丰富的活性位点,为反应物吸附和表面反应提供了更充足的场所,并且纳米纤维自身具有的一维结构,为光生电子提供了定向传输通道,使载流子沿纳米纤维轴向快速迁移,避免了在三维空间中的无序扩散与复合,而且纳米纤维直径极小,光生载流子从体相到表面的迁移路径大幅缩短,进一步降低了体相复合概率,从而可以有效提高光催化产H2O2的效率;然后通过1,3,5-三醛基间苯三酚与4,4'-二氨基二苯醚的缩聚反应,Tp分子含有三个羟基,在席夫碱反应生成亚胺键后,Tp上的羟基与相邻的亚胺氮原子形成分子内氢键,使亚胺键发生烯醇-酮互变异构并形成β-酮烯胺结构,该结构通过分子内氢键和扩展共轭体系获得高度稳定性,一旦形成后不易发生水解逆反应,在COF结晶过程中,缩合反应生成的微量水不仅不会破坏结构,反而有助于维持动态共价化学的可逆平衡,为框架的“错误检查与结构修复”提供必要的条件,有利于获得高结晶度的COF材料;通过在纳米纤维表面原位包覆多孔COF壳层,该COF壳层具有丰富的多孔结构,这些孔道可以将液体中的氧气分子富集到催化剂表面,提高局部氧气浓度,从而加速电子与氧气相遇并发生还原反应的过程,实现光催化产H2O2效率的提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of catalyst, in particular to a kind of fluorine ion modified TiO2 / COF photocatalyst and its preparation method, including the pretreatment of S1 titanium dioxide nanofiber, S2 titanium dioxide composite material is prepared, S3 surface treatment of titanium dioxide composite material and S4 in-situ formation COF coating on pretreated titanium dioxide composite material.The present application, by forming seed layer on the surface of titanium dioxide nanofiber, hydrothermal deposition fluorine-containing titanium dioxide nanoparticles and aldehyde group treatment as core, in-situ coating porous COF shell on the surface of core, obtain fluorine ion modified TiO2 / COF photocatalyst, not only show excellent photocatalytic H2O2 production efficiency, its unique structure design more give catalyst outstanding durability, so that it can continuously play catalytic role in long-term use, effectively improve the practical application potential of photocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, specifically to a fluoride ion modified TiO2 / COF photocatalyst and its preparation method. Background Technology

[0002] Photocatalytic synthesis of hydrogen peroxide (H2O2) has gained widespread attention as an important synthetic technique due to its significant advantages and its potential to replace traditional processes. This method utilizes semiconductor materials as catalysts and renewable resources such as solar energy to drive the reaction, increasing the efficiency of H2O2 production by promoting the catalytic action of oxygen and water. The main principle is that electrons are generated under light excitation, reducing oxygen molecules to superoxide radicals, which then undergo a protonation reaction to produce hydrogen peroxide. Holes provide protons to promote water oxidation, enabling the entire chemical reaction process without the need for complex equipment. Compared with traditional methods, photocatalysis has significant environmental advantages. In terms of energy supply, its main energy source is solar energy, which can significantly reduce the consumption of fossil fuels and is in line with the development direction of low-carbon and environmental protection. In terms of reaction medium, the reaction only uses oxygen and water, eliminating secondary pollution. Moreover, when the reaction system contains organic pollutants, organic wastewater can be used directly as the reaction medium. Photogenerated holes oxidize and degrade organic pollutants, while photogenerated electrons reduce dissolved oxygen to generate H2O2, simultaneously realizing the degradation of organic pollutants and the resource generation of H2O2. It shows good application prospects in the field of water pollution control and resource utilization.

[0003] Anatase titanium dioxide (TiO2) has been widely used in photocatalysis due to its excellent chemical stability, environmental friendliness, biocompatibility, and economic practicality. This compound has a wide bandgap of 3.0-3.2 eV; however, its inherent properties result in low absorption efficiency for visible light, limiting its photoelectric conversion to the ultraviolet band of solar radiation (accounting for less than 5%), thus restricting improvements in photoelectric conversion efficiency. Furthermore, rapid exciton recombination exacerbates the inefficiency of the charge separation process, making it difficult to significantly improve quantum efficiency. The low adsorption capacity of surface hydroxylated active sites for oxygen molecules also negatively impacts the hydrogen peroxide generation rate.

[0004] For example, Chinese patent CN114011467B discloses a mercaptopropionic acid-linked titanium dioxide covalent organic framework composite material, its preparation method, and its application. This technical solution combines inorganic semiconductor TiO2 with organic framework material COF nanosheets, which have a large π-conjugated system and good chemical stability, in the form of covalent bonds, thereby effectively improving the electron transfer rate and photocatalytic effect. However, when TiO2 particles are directly combined with organic framework material COF nanosheets in the form of covalent bonds, the TiO2 particles are unevenly covered on the COF surface, which leads to discontinuity at the heterojunction interface, severely hindering the migration of photogenerated electrons. This significantly reduces the charge separation efficiency of the S-type heterojunction. Furthermore, the electron migration path inside the nanoparticles is short and disordered, lacking directional fast transport channels, resulting in a higher probability of bulk recombination and reducing the number of photogenerated electrons participating in the surface reaction. This leads to unsatisfactory photocatalytic efficiency. Moreover, if the COF and particles are only bound by weak interaction forces, the structural stability is poor, causing the COF shell to easily peel off from the particle surface, resulting in catalyst deactivation and hindering the long-term recycling of the catalyst. Summary of the Invention

[0005] To address the problems existing in the prior art, the present invention aims to provide a fluoride ion modified TiO2 / COF photocatalyst and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a fluoride ion modified TiO2 / COF photocatalyst, specifically including the following steps: Pretreatment of S1 titanium dioxide nanofibers Titanium dioxide nanofibers were impregnated in titanium dioxide sol using an ultrasonic-assisted method, and then calcined to obtain pretreated titanium dioxide nanofibers. Preparation of S2 titanium dioxide composite material Tetrabutyl titanate was added to a mixed solution of concentrated nitric acid and deionized water, and then ammonium fluoride was added. After mixing, a precursor solution was obtained. Then, pretreated titanium dioxide nanofibers were immersed in the precursor solution and reacted for 9-12 hours. The product was calcined to obtain a titanium dioxide composite material. Surface treatment of S3 titanium dioxide composite material 1) Add the titanium dioxide composite material to anhydrous toluene and disperse it evenly. Then add 3-aminopropyltriethoxysilane, mix well, and heat under reflux for 12-15 hours to obtain the aminated titanium dioxide composite material. 2) The aminated titanium dioxide composite material was added to anhydrous ethanol, dispersed evenly, and then 1,3,5-trialdehyde phloroglucinol was added. Acetic acid was added dropwise, and the mixture was heated under reflux for 4-6 hours to obtain the pretreated titanium dioxide composite material. In-situ COF coating layer formed on S4 pretreated titanium dioxide composite material 1,3,5-trialdehyde phloroglucinol and 4,4'-diaminodiphenyl ether are dissolved in a mixed solvent composed of 1,4-dioxane, mesitylene and acetic acid to obtain a reaction solution. The pretreated titanium dioxide composite material is then immersed in the reaction solution and reacted for 72-75 hours to obtain a fluoride-modified TiO2 / COF photocatalyst.

[0007] As a further preferred embodiment of the present invention, in S1, the titanium dioxide sol is specifically prepared as follows: Add tetrabutyl titanate to anhydrous ethanol while stirring continuously at 150-200 rpm, then add glacial acetic acid and stir for 15-30 min to obtain a tetrabutyl titanate ethanol solution. Subsequently, mix deionized water and anhydrous ethanol, and add concentrated nitric acid dropwise to adjust the pH value to 2-3 to obtain a mixed solution. Add the mixed solution to the tetrabutyl titanate ethanol solution while stirring at 800-1000 rpm and continue stirring for 1-2 h.

[0008] Furthermore, in the tetrabutyl titanate ethanol solution, the volume ratio of tetrabutyl titanate, anhydrous ethanol, and glacial acetic acid is (5-10):(50-80):(2-3). In the mixture, the volume ratio of deionized water to anhydrous ethanol is (1-2):(10-15). The volume ratio of the mixture to the tetrabutyl titanate ethanol solution is (11-17):(57-93).

[0009] As a further preferred embodiment of the present invention, in S1, the calcination temperature is 450-500℃ and the calcination time is 1-2h.

[0010] As a further preferred embodiment of the present invention, in S2, the ratio of tetrabutyl titanate, concentrated nitric acid, deionized water and ammonium fluoride in the precursor solution is (2-3) mL: (12-16) mL: (24-28) mL: (40-60) mg; The ratio of the pretreated titanium dioxide nanofibers to the precursor solution is (2-3) g: (42-70) mL; The reaction is carried out at a temperature of 150-160℃; The calcination is carried out at a temperature of 350-370℃ for 1-2 hours.

[0011] As a further preferred embodiment of the present invention, in S3-1), the ratio of the titanium dioxide composite material, anhydrous toluene, and 3-aminopropyltriethoxysilane is (2-3) g: (150-200) mL: (2-5) mL; The heating reflux reaction is carried out at a temperature of 110-115℃.

[0012] As a further preferred embodiment of the present invention, in S3-2), the ratio of the aminated titanium dioxide composite material, anhydrous ethanol, 1,3,5-trialdehyde phloroglucinol, and acetic acid is (1.5-2.0) g : (80-120) mL : (0.05-0.10) g : (0.1-0.2) mL; The acetic acid has a concentration of 6-8 mol / L; The heating reflux temperature is 80-85℃.

[0013] As a further preferred embodiment of the present invention, in S4, the ratio of 1,3,5-trialdehyde phloroglucinol, 4,4'-diaminodiphenyl ether, 1,4-dioxane, mesitylene, and acetic acid in the reaction solution is (0.63-0.72) g : (0.82-1.03) g : (15-25) mL : (15-25) mL : (0.3-0.5) mL; The acetic acid has a concentration of 6-8 mol / L.

[0014] As a further preferred embodiment of the present invention, in S4, the ratio of the pretreated titanium dioxide composite material to the reaction solution is (0.1-0.2) g : (30-50) mL; The reaction is carried out at a temperature of 120-130℃.

[0015] A fluoride ion modified TiO2 / COF photocatalyst is prepared by the method described in any one of claims 1-9.

[0016] Compared with the prior art, the beneficial effects of the present invention are: In this invention, titanium dioxide nanofibers are used as the core. Their high specific surface area provides more active sites, offering ample space for reactant adsorption and surface reactions. Furthermore, the one-dimensional structure of the nanofibers provides directional transport channels for photogenerated electrons, enabling rapid migration of charge carriers along the nanofiber axis and avoiding disordered diffusion and recombination in three-dimensional space. Moreover, the extremely small diameter of the nanofibers significantly shortens the migration path of photogenerated charge carriers from the bulk phase to the surface, further reducing the probability of bulk recombination and thus effectively improving the efficiency of photocatalytic H2O2 production. Then, through the condensation reaction of 1,3,5-trialdehyde phloroglucinol with 4,4'-diaminodiphenyl ether, the Tp molecule contains three hydroxyl groups. After the formation of imine bonds in the Schiff base reaction, the hydroxyl groups on Tp bond with the adjacent imine nitrogen atoms. Intramolecular hydrogen bonds are formed, causing the imine bonds to undergo enol-ketone tautomerism and form a β-ketoenamine structure. This structure achieves high stability through intramolecular hydrogen bonds and an extended conjugated system. Once formed, it is not prone to hydrolysis reversal reactions. During COF crystallization, the trace amounts of water generated by the condensation reaction not only do not destroy the structure, but also help maintain the reversible equilibrium of dynamic covalent chemistry, providing the necessary conditions for the "error checking and structural repair" of the framework, which is beneficial for obtaining COF materials with high crystallinity. By in-situ coating the surface of nanofibers with a porous COF shell, which has a rich porous structure, oxygen molecules in the liquid can be enriched on the catalyst surface, increasing the local oxygen concentration, thereby accelerating the process of electrons meeting oxygen and undergoing reduction reaction, thus improving the efficiency of photocatalytic H2O2 production.

[0017] To further improve the efficiency of photocatalytic H2O2 production and enhance the stability of the photocatalyst structure for long-term use, this invention also treats titanium dioxide nanofibers. Through sol impregnation and calcination, a titanium dioxide nanoparticle film (seed layer) is formed on the surface of the titanium dioxide nanofibers, providing high-density nucleation sites for subsequent hydrothermal growth and ensuring uniform and robust nanoparticle growth. Subsequently, ammonium fluoride is introduced during hydrothermal nanoparticle growth, and calcination allows fluorine ions to be doped into the titanium dioxide lattice, thereby depositing fluorine-containing titanium dioxide nanoparticles on the surface of the titanium dioxide nanofibers. The deposited nanoparticles form a raised, rough structure on the surface of the titanium dioxide nanofibers. On the one hand, during subsequent COF polymerization, the nanoparticles distributed on the fiber surface can be effectively embedded and encapsulated within the COF shell. This forces the COF shell to overcome the interfacial frictional resistance generated by the embedded nanoparticles during desorption, significantly improving the bonding strength of the COF shell on the nanofiber matrix. Simultaneously, when the COF shell is subjected to stress, the dispersed nanoparticles can... By dispersing concentrated stress, the formation of microcracks caused by stress concentration is effectively suppressed, thereby improving the stability of the COF shell structure and ensuring its structural integrity during long-term photocatalytic operation. This maintains the tight contact of the S-type heterojunction interface and ensures stable and efficient interfacial charge transfer. On the other hand, the deposited nanoparticles not only significantly increase the specific surface area and expose more highly active atomic sites, providing more sufficient attachment and reaction sites for reactants, but also shorten the migration path of photogenerated carriers, constructing a continuous and efficient short-range electron transport pathway. This effectively reduces the probability of bulk recombination of photogenerated electrons and holes, allowing more effective carriers to quickly migrate to the material surface to participate in the catalytic reaction, thus effectively improving the efficiency of photocatalytic H2O2 production. Moreover, by doping with fluorine ions, on the one hand, a large number of oxygen vacancies can be induced in the titanium dioxide lattice. These oxygen vacancies introduce new electronic states near the conduction band bottom within the band gap, effectively narrowing the band gap and extending the photoresponse range into the visible light region, improving solar energy utilization. On the other hand, it can also induce the formation of Ti. 3+The defects, acting as electron-trapping centers, effectively capture photogenerated electrons, delaying their recombination with holes in the bulk phase, thereby extending carrier lifetime. Furthermore, it can shift the d-band center of TiO2 upwards, enhancing the chemisorption strength of oxygen molecules on the TiO2 surface, increasing the enrichment concentration and activation efficiency of oxygen on the catalyst surface, and accelerating the kinetics of two-electron oxygen reduction to produce H2O2, thus further improving the efficiency of photocatalytic H2O2 production. Next, through APTES grafting and the Schiff base reaction of 1,3,5-trialdehyde phloroglucinol, aldehyde functional groups are introduced onto the composite material surface, providing chemical grafting sites for subsequent in-situ growth of COF. This allows the COF shell to be more firmly bonded to the substrate through covalent bonds, significantly reducing the interfacial charge transport barrier and ensuring the directional migration path of photogenerated carriers, thereby further improving the efficiency of photocatalytic H2O2 production.

[0018] In this invention, a fluoride-modified TiO2 / COF photocatalyst is obtained by forming a seed layer on the surface of titanium dioxide nanofibers, hydrothermally depositing fluorine-containing titanium dioxide nanoparticles, and using aldehyde-modified particles as the core. A porous COF shell is then coated in situ on the surface of the core. This catalyst can be used for photocatalytic H2O2 production in pure water systems, as well as for pollutant degradation and H2O2 resource generation in organic wastewater treatment processes. It not only exhibits excellent photocatalytic H2O2 production efficiency, but its unique structural design also endows the catalyst with excellent durability, enabling it to continuously exert its catalytic effect during long-term use and effectively enhancing the practical application potential of the photocatalyst. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is the standard curve of the absorbance-H2O2 concentration relationship in this invention. Detailed Implementation

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] In this embodiment of the invention, the titanium dioxide nanofibers have a diameter of 100-200 nm, a length of 10-15 µm, and a specific surface area of ​​15-30 m². 2 / g, purity ≥99%, anatase phase.

[0023] In this embodiment of the invention, the concentrated nitric acid has a mass fraction of 68%.

[0024] Example 1 A method for preparing a fluoride ion modified TiO2 / COF photocatalyst, the specific steps of which are as follows: 1) Tetrabutyl titanate was added to anhydrous ethanol under continuous stirring at 150 r / min, and glacial acetic acid was added as a hydrolysis inhibitor. The mixture was stirred for 15 min to obtain a tetrabutyl titanate ethanol solution, in which the volume ratio of tetrabutyl titanate, anhydrous ethanol, and glacial acetic acid was 5:50:2. Then, deionized water and anhydrous ethanol were mixed, and concentrated nitric acid was added dropwise to adjust the pH to 2 to obtain a mixed solution, in which the volume ratio of deionized water to anhydrous ethanol was 1:10. The mixed solution was added to the tetrabutyl titanate ethanol solution under stirring at 800 r / min, and the mixture was stirred for 1 h to obtain titanium dioxide sol, in which the volume ratio of the mixed solution to the tetrabutyl titanate ethanol solution was 11:57. 2) After cleaning the titanium dioxide nanofibers with deionized water and anhydrous ethanol, they were vacuum dried at 70℃ for 2 hours. Then, using an ultrasonic-assisted method, the dried titanium dioxide nanofibers were completely immersed in titanium dioxide sol at a mass-to-volume ratio of 1g:60mL. The mixture was ultrasonically treated at 100W for 10 minutes, centrifuged at 3000r / min for 3 minutes, and the supernatant was discarded. The nanofibers were ultrasonically washed with anhydrous ethanol for 2 minutes, centrifuged again at 3000r / min for 3 minutes, and the supernatant was discarded. The washing with anhydrous ethanol was repeated twice. The collected fibers were taken out and spread out, placed at room temperature for 30 minutes, and dried at 80℃ for 1 hour. The above steps of immersion-ultrasonic treatment-centrifugation-ethanol washing-centrifugation-spreading-drying were repeated 3 times. After the last drying, the temperature was raised to 450℃ in air at a heating rate of 1℃ / min and calcined for 1 hour. Then, the mixture was naturally cooled to room temperature to obtain pretreated titanium dioxide nanofibers. 3) Tetrabutyl titanate was added to a mixed solution of concentrated nitric acid and deionized water under stirring in an ice-water bath at 100 r / min, followed by the addition of ammonium fluoride. The mixture was stirred for 30 min to obtain a precursor solution. The ratio of tetrabutyl titanate, concentrated nitric acid, deionized water and ammonium fluoride was 2 mL: 12 mL: 28 mL: 40 mg. Then, the pretreated titanium dioxide nanofibers were immersed in the precursor solution at a mass-volume ratio of 1 g: 21 mL. The nanofibers were transferred to a reaction vessel, sealed, and reacted at 150 °C for 9 h. After the reaction was completed, the mixture was naturally cooled to room temperature. The nanofibers were then washed three times with deionized water and anhydrous ethanol, dried at 60 °C for 12 h, and then calcined at 350 °C in air at a heating rate of 1 °C / min for 1 h. The mixture was then naturally cooled to room temperature to obtain the titanium dioxide composite material. 4) The titanium dioxide composite material was added to anhydrous toluene and ultrasonically dispersed at 100W for 5 min. Then, 3-aminopropyltriethoxysilane was added under stirring at 80 r / min. After mixing, the mixture was heated to reflux at 110℃ for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was naturally cooled to room temperature, washed 5 times alternately with deionized water and anhydrous ethanol, and dried at 60℃ for 10 h to obtain the aminated titanium dioxide composite material. The ratio of titanium dioxide composite material, anhydrous toluene, and 3-aminopropyltriethoxysilane was 2 g: 150 mL: 2 mL. 5) The aminated titanium dioxide composite material was added to anhydrous ethanol and ultrasonically dispersed at 100W for 5 min. Then, 1,3,5-trialdehyde phloroglucinol was added and stirred to dissolve. Acetic acid with a concentration of 6 mol / L was added dropwise as a catalyst, and the mixture was heated to reflux at 80℃ for 4 h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed 5 times alternately with deionized water and anhydrous ethanol, and then dried at 60℃ for 10 h to obtain the pretreated titanium dioxide composite material. The ratio of aminated titanium dioxide composite material, anhydrous ethanol, 1,3,5-trialdehyde phloroglucinol, and acetic acid was 1.5 g: 80 mL: 0.05 g: 0.1 mL. 6) Dissolve 1,3,5-trialdehyde phloroglucinol and 4,4'-diaminodiphenyl ether in a mixed solvent of 1,4-dioxane, mesitylene, and 6 mol / L acetic acid. Stir at 100 rpm until completely dissolved to obtain a reaction solution. The ratio of 1,3,5-trialdehyde phloroglucinol, 4,4'-diaminodiphenyl ether, 1,4-dioxane, mesitylene, and acetic acid is 0.63 g:0.82 g:15 mL:15 mL:0.3 mL. Then, immerse the pretreated titanium dioxide composite material in the reaction solution at a weight-to-volume ratio of 0.1 g:30 mL and stir at 100 rpm for 10 minutes. After 1 minute, insert a nitrogen tube below the liquid surface and introduce high-purity nitrogen at a flow rate of 100 mL / min, while simultaneously supplementing with intermittent ultrasonic bubbling (200W ultrasonic for 1 minute, 2 minutes interval, and circulation), and continue ventilating for 30 minutes to simultaneously remove gaseous oxygen and dissolved oxygen in the liquid phase. After deoxygenation, place the product in a reaction vessel, seal it, and react at 120℃ for 72 hours. After the reaction, allow it to cool naturally, remove the product, wash it three times in sequence with DMF, anhydrous ethanol, and acetone, and then wash it with THF in a Soxhlet extractor for 24 hours to remove unreacted monomers. After vacuum drying at 60℃ for 12 hours, the fluoride ion modified TiO2 / COF photocatalyst can be obtained.

[0025] Example 2 A method for preparing a fluoride ion modified TiO2 / COF photocatalyst, the specific steps of which are as follows: 1) Tetrabutyl titanate was added to anhydrous ethanol under continuous stirring at 150 r / min, and glacial acetic acid was added as a hydrolysis inhibitor. The mixture was stirred for 15 min to obtain a tetrabutyl titanate ethanol solution, in which the volume ratio of tetrabutyl titanate, anhydrous ethanol, and glacial acetic acid was 5:50:2. Then, deionized water and anhydrous ethanol were mixed, and concentrated nitric acid was added dropwise to adjust the pH to 2 to obtain a mixed solution, in which the volume ratio of deionized water to anhydrous ethanol was 1:10. The mixed solution was added to the tetrabutyl titanate ethanol solution under stirring at 800 r / min, and the mixture was stirred for 1 h to obtain titanium dioxide sol, in which the volume ratio of the mixed solution to the tetrabutyl titanate ethanol solution was 11:57. 2) After cleaning the titanium dioxide nanofibers with deionized water and anhydrous ethanol, they were vacuum dried at 70℃ for 2 hours. Then, using an ultrasonic-assisted method, the dried titanium dioxide nanofibers were completely immersed in titanium dioxide sol at a mass-to-volume ratio of 1g:60mL. The mixture was ultrasonically treated at 100W for 10 minutes, centrifuged at 3000r / min for 3 minutes, and the supernatant was discarded. The nanofibers were ultrasonically washed with anhydrous ethanol for 2 minutes, centrifuged again at 3000r / min for 3 minutes, and the supernatant was discarded. The washing with anhydrous ethanol was repeated twice. The collected fibers were taken out and spread out, placed at room temperature for 30 minutes, and dried at 80℃ for 1 hour. The above steps of immersion-ultrasonic treatment-centrifugation-ethanol washing-centrifugation-spreading-drying were repeated 3 times. After the last drying, the temperature was raised to 450℃ in air at a heating rate of 1℃ / min and calcined for 1 hour. Then, the mixture was naturally cooled to room temperature to obtain pretreated titanium dioxide nanofibers. 3) Tetrabutyl titanate was added to a mixed solution of concentrated nitric acid and deionized water under stirring in an ice-water bath at 100 r / min, followed by the addition of ammonium fluoride. The mixture was stirred for 30 min to obtain a precursor solution. The ratio of tetrabutyl titanate, concentrated nitric acid, deionized water and ammonium fluoride was 2 mL: 12 mL: 28 mL: 40 mg. Then, the pretreated titanium dioxide nanofibers were immersed in the precursor solution at a mass-volume ratio of 1 g: 21 mL. The nanofibers were transferred to a reaction vessel, sealed, and reacted at 150 °C for 9 h. After the reaction was completed, the mixture was naturally cooled to room temperature. The nanofibers were then washed three times with deionized water and anhydrous ethanol, dried at 60 °C for 12 h, and then calcined at 350 °C in air at a heating rate of 1 °C / min for 1 h. The mixture was then naturally cooled to room temperature to obtain the titanium dioxide composite material. 4) The titanium dioxide composite material was added to anhydrous toluene and ultrasonically dispersed at 100W for 5 min. Then, 3-aminopropyltriethoxysilane was added under stirring at 80 r / min. After mixing, the mixture was heated to reflux at 110℃ for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was naturally cooled to room temperature, washed 5 times alternately with deionized water and anhydrous ethanol, and dried at 60℃ for 10 h to obtain the aminated titanium dioxide composite material. The ratio of titanium dioxide composite material, anhydrous toluene, and 3-aminopropyltriethoxysilane was 2 g: 150 mL: 2 mL. 5) The aminated titanium dioxide composite material was added to anhydrous ethanol and ultrasonically dispersed at 100W for 5 min. Then, 1,3,5-trialdehyde phloroglucinol was added and stirred to dissolve. Acetic acid with a concentration of 6 mol / L was added dropwise as a catalyst, and the mixture was heated to reflux at 80℃ for 4 h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed 5 times alternately with deionized water and anhydrous ethanol, and then dried at 60℃ for 10 h to obtain the pretreated titanium dioxide composite material. The ratio of aminated titanium dioxide composite material, anhydrous ethanol, 1,3,5-trialdehyde phloroglucinol, and acetic acid was 1.5 g: 80 mL: 0.05 g: 0.1 mL. 6) Dissolve 1,3,5-trialdehyde phloroglucinol and 4,4'-diaminodiphenyl ether in a mixed solvent of 1,4-dioxane, mesitylene, and 6 mol / L acetic acid. Stir at 120 rpm until completely dissolved to obtain a reaction solution. The ratio of 1,3,5-trialdehyde phloroglucinol, 4,4'-diaminodiphenyl ether, 1,4-dioxane, mesitylene, and acetic acid is 0.63 g:0.82 g:15 mL:15 mL:0.3 mL. Then, immerse the pretreated titanium dioxide composite material in the reaction solution at a weight-to-volume ratio of 0.1 g:30 mL and stir at 100 rpm for 10 min. Transfer the mixture to a Pyrex container. Inside the glass tube, a three-cycle process of liquid nitrogen freezing-vacuuming-thawing was performed to thoroughly remove dissolved gases and volatile water from the gaseous and liquid phases. After the cycle, the Pyrex glass tube was flame-sealed under vacuum. After sealing, it was placed in an oven and reacted at 120°C for 72 hours. After the reaction, it was allowed to cool naturally. The Pyrex glass tube was then opened to remove the product, which was washed three times in sequence with DMF, anhydrous ethanol, and acetone. Then, it was washed with THF in a Soxhlet extractor for 24 hours to remove unreacted monomers. After vacuum drying at 60°C for 12 hours, the fluoride-modified TiO2 / COF photocatalyst was obtained.

[0026] Example 3 A method for preparing a fluoride ion modified TiO2 / COF photocatalyst, the specific steps of which are as follows: 1) Tetrabutyl titanate was added to anhydrous ethanol under continuous stirring at 200 r / min, and glacial acetic acid was added as a hydrolysis inhibitor. The mixture was stirred for 30 min to obtain a tetrabutyl titanate ethanol solution, in which the volume ratio of tetrabutyl titanate, anhydrous ethanol, and glacial acetic acid was 10:80:3. Then, deionized water and anhydrous ethanol were mixed, and concentrated nitric acid was added dropwise to adjust the pH to 3 to obtain a mixed solution, in which the volume ratio of deionized water to anhydrous ethanol was 2:15. The mixed solution was added to the tetrabutyl titanate ethanol solution under stirring at 1000 r / min, and the mixture was stirred for 2 h to obtain titanium dioxide sol, in which the volume ratio of the mixed solution to the tetrabutyl titanate ethanol solution was 17:93. 2) After cleaning the titanium dioxide nanofibers with deionized water and anhydrous ethanol, they were vacuum dried at 80℃ for 3h. Then, using an ultrasonic-assisted method, the dried titanium dioxide nanofibers were completely immersed in titanium dioxide sol at a mass-volume ratio of 1g:60mL. The mixture was ultrasonically treated at 150W for 20min, centrifuged at 4000r / min for 5min, and the supernatant was discarded. The nanofibers were ultrasonically washed with anhydrous ethanol for 5min, centrifuged again at 4000r / min for 5min, and the supernatant was discarded. The washing with anhydrous ethanol was repeated 3 times. The collected fibers were taken out and spread out, placed at room temperature for 50min, and dried at 90℃ for 2h. The above steps of immersion-ultrasonic treatment-centrifugation-ethanol washing-centrifugation-spreading-drying were repeated 3 times. After the last drying, the temperature was raised to 500℃ in air at a heating rate of 2℃ / min and calcined for 2h. Then, the nanofibers were naturally cooled to room temperature to obtain pretreated titanium dioxide nanofibers. 3) Tetrabutyl titanate was added to a mixed solution of concentrated nitric acid and deionized water under stirring in an ice-water bath at 150 r / min, followed by the addition of ammonium fluoride. The mixture was stirred for 50 min to obtain a precursor solution. The ratio of tetrabutyl titanate, concentrated nitric acid, deionized water and ammonium fluoride was 3 mL: 16 mL: 24 mL: 60 mg. Then, according to the mass-volume ratio of 3 g: 70 mL, the pretreated titanium dioxide nanofibers were immersed in the precursor solution, transferred to a reaction vessel, sealed, and reacted at 160 °C for 12 h. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged, and washed three times with deionized water and anhydrous ethanol. After drying at 70 °C for 15 h, the mixture was heated to 370 °C at a heating rate of 2 °C / min in air and calcined for 2 h. After natural cooling to room temperature, the titanium dioxide composite material was obtained. 4) Add the titanium dioxide composite material to anhydrous toluene and disperse it by ultrasonication at 200W for 10 min. Then, add 3-aminopropyltriethoxysilane while stirring at 120 r / min. After mixing, heat and reflux at 115℃ for 15 h under nitrogen atmosphere. After the reaction is completed, cool naturally to room temperature, wash with deionized water and anhydrous ethanol alternately 5 times, and dry at 70℃ for 15 h to obtain the aminated titanium dioxide composite material. The ratio of titanium dioxide composite material, anhydrous toluene and 3-aminopropyltriethoxysilane is 3 g: 200 mL: 5 mL. 5) The aminated titanium dioxide composite material was added to anhydrous ethanol and ultrasonically dispersed at 200W for 10 min. Then, 1,3,5-trialdehyde phloroglucinol was added and stirred to dissolve. Acetic acid with a concentration of 8 mol / L was added dropwise as a catalyst, and the mixture was heated to reflux at 85℃ for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed 5 times alternately with deionized water and anhydrous ethanol, and then dried at 70℃ for 15 h to obtain the pretreated titanium dioxide composite material. The ratio of aminated titanium dioxide composite material, anhydrous ethanol, 1,3,5-trialdehyde phloroglucinol, and acetic acid was 2 g: 120 mL: 0.1 g: 0.2 mL. 6) Dissolve 1,3,5-trialdehyde phloroglucinol and 4,4'-diaminodiphenyl ether in a mixed solvent of 1,4-dioxane, mesitylene, and 8 mol / L acetic acid. Stir at 150 rpm until completely dissolved to obtain a reaction solution. The ratio of 1,3,5-trialdehyde phloroglucinol, 4,4'-diaminodiphenyl ether, 1,4-dioxane, mesitylene, and acetic acid is 0.72 g: 1.03 g: 25 mL: 25 mL: 0.5 mL. Then, according to a weight-volume ratio of 0.2 g: 50 mL, immerse the pretreated titanium dioxide composite material in the reaction solution and stir at 150 rpm for 2 minutes. 0 min, then insert the nitrogen tube below the liquid surface, and introduce high-purity nitrogen at a flow rate of 200 mL / min, while intermittent ultrasonic bubbling (200W ultrasonic for 1 min, 2 min interval, cycle), and continue to ventilate for 30 min to simultaneously remove gaseous oxygen and liquid dissolved oxygen. After deoxygenation, place it in a reaction vessel, seal it, and react at 130℃ for 75 h. After the reaction, allow it to cool naturally, take out the product, wash it three times in sequence with DMF, anhydrous ethanol, and acetone, and then wash it with THF in a Soxhlet extractor for 30 h to remove unreacted monomers. After vacuum drying at 70℃ for 15 h, the fluoride ion modified TiO2 / COF photocatalyst can be obtained.

[0027] Comparative Example 1: This comparative example is basically the same as Example 1, except that steps 1)-5) are omitted. After cleaning the titanium dioxide nanofibers with deionized water and anhydrous ethanol, they are vacuum dried at 70°C for 2 hours, replacing the pretreated titanium dioxide composite material in step 6).

[0028] Comparative Example 2: This comparative example is basically the same as Example 1, except that steps 1)-2) are omitted. After cleaning the titanium dioxide nanofibers with deionized water and anhydrous ethanol, they are vacuum dried at 70°C for 2 hours, which replaces the pretreated titanium dioxide nanofibers in step 3).

[0029] Comparative Example 3: This comparative example is basically the same as Example 1, except that steps 1)-3) are omitted. After cleaning the titanium dioxide nanofibers with deionized water and anhydrous ethanol, they are vacuum dried at 70°C for 2 hours to replace the titanium dioxide composite material in step 4).

[0030] Comparative Example 4: This comparative example is basically the same as Example 1, except that ammonium fluoride in step 3) is omitted.

[0031] Comparative Example 5: This comparative example is basically the same as Example 1, except that steps 4)-5) are omitted and titanium dioxide composite material is used instead of the pretreated titanium dioxide composite material in step 6).

[0032] Control group: 1,3,5-trialdehyde phloroglucinol and 4,4'-diaminodiphenyl ether were dissolved in a mixed solvent of 1,4-dioxane, mesitylene, and 6 mol / L acetic acid. The solution was stirred at 100 rpm until completely dissolved to obtain a reaction solution. The ratio of 1,3,5-trialdehyde phloroglucinol, 4,4'-diaminodiphenyl ether, 1,4-dioxane, mesitylene, and acetic acid was 0.63 g:0.82 g:15 mL:15 mL:0.3 mL. Subsequently, titanium dioxide nanoparticles (particle size 20-50 nm, purity ≥99%, anatase phase) were immersed in the solution at a weight-volume ratio of 0.1 g:30 mL. Add the product to the reaction solution and stir at 100 rpm for 10 min. Then, insert a nitrogen tube below the liquid surface and introduce high-purity nitrogen at a flow rate of 100 mL / min, while simultaneously using intermittent ultrasonic bubbling (200 W ultrasonic for 1 min, 2 min interval, and circulation). Continue purging for 30 min to simultaneously remove gaseous oxygen and dissolved oxygen from the liquid phase. After deoxygenation, place the product in a reaction vessel, seal it, and react at 120℃ for 72 h. After the reaction, allow it to cool naturally, remove the product, and wash it three times in sequence with DMF, anhydrous ethanol, and acetone. Then, wash it with THF in a Soxhlet extractor for 24 h to remove unreacted monomers. Finally, dry it under vacuum at 60℃ for 12 h to obtain the photocatalyst.

[0033] Test experiment: H2O2 yield test I. Experimental Procedure 1. Photocatalyst samples were prepared using the methods of Examples 1-3, Comparative Examples 1-5, and the control group. Then, 10.0 mg of each photocatalyst sample was weighed and placed in a flask. 5 mL of anhydrous ethanol and 45 mL of deionized water were added, and the sample was ultrasonically dispersed at 100 W for 10 min with a magnetic stir bar to obtain a uniform catalyst suspension (catalyst concentration 0.2 g / L). 2. Place the flask on a constant temperature magnetic stirrer, insert the oxygen delivery tube and sampling syringe, and stir at 600 r / min for 30 min under light-protected conditions to allow the catalyst and reaction solution to reach adsorption-desorption equilibrium. Before light exposure, take 1 mL of the suspension with a pipette and filter it through a 0.22 μm hydrophilic PTFE membrane. The filtrate is used as a "zero point" sample to subtract the interference of dark adsorption on H2O2 detection. Then, continuously introduce high-purity oxygen into the reaction solution at a flow rate of 100 mL / min for 15 min to saturate the reaction solution with oxygen. Maintain continuous oxygen supply throughout the reaction. 3) Turn on the 300W xenon lamp (equipped with an AM 1.5G filter, light intensity 100mW / cm²), start the photo-reaction and start timing. Maintain magnetic stirring at 600r / min throughout the reaction. Control the reaction temperature at 25±1℃ through a circulating water bath. The total reaction time is 60min. 4) After the light reaction begins, take 1 mL of the reaction suspension every 15 min with a pipette and immediately filter it through a 0.22 μm hydrophilic PTFE syringe filter. Collect the filtrate in a centrifuge tube. After each sampling, add 1 mL of deionized water to the reaction flask to maintain a constant total volume of the reaction solution. Take samples 4 times after light exposure (15, 30, 45, and 60 min), plus the zero-point sample before light exposure, for a total of 5 time points. 5) Take 0.2 mL of the above filtrate, add 0.8 mL of deionized water and mix well (5-fold dilution). Then take 1 mL of the diluted filtrate and mix it with 1 mL of potassium titanium oxalate colorimetric solution. Make up to 5 mL with deionized water, shake well, and let stand at room temperature in the dark for 10 min. Using the solution after the same colorimetric steps of 0 μmol / L standard solution as a reference, measure the absorbance of the sample at 400 nm using a UV-Vis spectrophotometer. Calculate the H2O2 concentration at each time point based on the standard curve of absorbance-concentration relationship.

[0034] The yield of H2O2 is calculated using the following formula: S=(C×V) / (m×t). Among them, the yield of S-H2O2 (μmol.g) -1 .h -1 ), C - The actual concentration of H2O2 in the original filtrate (μmol / L), which is the concentration after dilution (calculated from the standard curve) × dilution factor. V - Total volume of the reaction solution (0.050L) m-catalyst mass (0.010 g), t - light reaction time (h).

[0035] II. Plotting the H2O2 Standard Curve 1) The standard curve for H2O2 was plotted using the potassium titanium oxalate method. Potassium titanium oxalate colorimetric solution: Accurately weigh 1.0 g of potassium titanium oxalate, dissolve it in 50 mL of deionized water, add 5 mL of concentrated sulfuric acid (98%), and dilute to 100 mL with deionized water. Shake well and set aside. H2O2 standard solution: Take 0.5 mL of 30% H2O2 and dilute it to 100 mL with deionized water to obtain H2O2 stock solution. Then titrate it with 0.02 mol / L KMnO4 standard solution to determine its accurate concentration. Then dilute it stepwise to prepare a 100 μmol / L standard working solution. 2) Take the above 100 μmol / L H₂O₂ standard working solution and dilute it stepwise with deionized water to prepare a series of H₂O₂ standard solutions with concentrations of 0 μmol / L, 10 μmol / L, 20 μmol / L, 30 μmol / L, 40 μmol / L, 50 μmol / L, 60 μmol / L, 80 μmol / L, and 100 μmol / L. Take nine 10 mL colorimetric tubes, add 1 mL of the above standard series solutions of different concentrations to each, add 1 mL of potassium titanium oxalate colorimetric solution to each, and dilute to 5 mL with deionized water. Shake well and let stand at room temperature in the dark for 10 min. Using the blank solution (0 μmol / L) as a reference, measure the absorbance of each solution at 400 nm using a UV-Vis spectrophotometer, and then plot a standard curve. Figure 1 As shown.

[0036] Standard curve equation: A = 0.00878 × C 稀释后 (R) 2 =0.9997). Where A is the absorbance at 400 nm, and C 稀释后 H2O2 concentration (μmol / L) The formula for calculating the concentration of H2O2 in the sample is as follows: C 稀释后 =(A1-A0) / 0.00878, A1 - The absorbance of the diluted sample measured at 400 nm. A0 - The absorbance of the blank sample measured at 400 nm. C 原始 =C 稀释后 ×5 By using A1-A0, background absorption caused by reagents, solvents, etc., can be eliminated, making the calculation results more accurate.

[0037] The experimental results are shown in Table 1. Table 1. Yield of H2O2 Photocatalyst durability test The photocatalytic reaction was carried out under light irradiation for 60 minutes according to the above-described photocatalytic experimental method. The H2O2 yield was recorded as the data for the first cycle. After the reaction, the photocatalyst was collected by centrifugation at 3000 r / min for 3 min, transferred to a beaker, and washed three times with 30 mL of deionized water (5 min each time) and three times with 30 mL of anhydrous ethanol (5 min each time). The washed catalyst was then dried in a vacuum oven at 60 °C for 12 h. The dried catalyst was redispersed in fresh reaction solution, and the photocatalytic reaction was repeated according to the above-described photocatalytic experimental method. Each cycle involved sampling, replenishment, recovery, washing, and drying using the same method, for a total of 10 cycles. The H2O2 yield was recorded after each cycle, and the yield retention rate was calculated using the following formula. Yield retention rate = C 10 / C1×100% Among them, C 10 It is the yield after 10 cycles. C1 is the yield of the first yield; The results are shown in Table 2. Table 2 Yield Retention Rate As shown in Tables 1 and 2, the photocatalyst in this invention exhibits high efficiency in the photocatalytic production of H₂O₂, achieving a yield of 2500 μmol·g⁻¹ under simulated sunlight irradiation. -1 ·h -1 Furthermore, it exhibits good structural stability, maintaining a yield retention rate of ≥87% after 10 cycles of use. This allows it to continuously exert its catalytic effect during long-term use, effectively enhancing the practical application potential of photocatalysts.

[0038] Furthermore, in this invention, Example 1 employs a nitrogen-intermittent ultrasonic bubbling-assisted deoxygenation reactor process. Although this process is slightly inferior to the vacuum tube sealing process in Example 2 in terms of deoxygenation and dehydration effects, it has significant advantages in scale-up production: the equipment is simple, the operation is convenient, the batch processing capacity is large, and it can effectively control the uniform growth of the COF shell on the TiO2 surface, obtain a β-ketoenamine type COF thin shell with good crystallinity, construct an effective heterojunction, and achieve excellent photocatalytic H2O2 production performance. For most industrial applications, the reactor process is sufficient to achieve catalytic performance and cycle stability comparable to the vacuum tube process. Therefore, this invention prefers to use the reactor process, which combines excellent catalytic performance with industrial scale-up feasibility and is more in line with actual production needs.

[0039] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a fluoride ion-modified TiO2 / COF photocatalyst, characterized in that, Specifically, the steps include the following: Pretreatment of S1 titanium dioxide nanofibers Titanium dioxide nanofibers were impregnated in titanium dioxide sol using an ultrasonic-assisted method, and then calcined to obtain pretreated titanium dioxide nanofibers. Preparation of S2 titanium dioxide composite material Tetrabutyl titanate was added to a mixed solution of concentrated nitric acid and deionized water, and then ammonium fluoride was added. After mixing, a precursor solution was obtained. Then, pretreated titanium dioxide nanofibers were immersed in the precursor solution and reacted for 9-12 hours. The product was calcined to obtain a titanium dioxide composite material. Surface treatment of S3 titanium dioxide composite material 1) Add the titanium dioxide composite material to anhydrous toluene and disperse it evenly. Then add 3-aminopropyltriethoxysilane, mix well, and heat under reflux for 12-15 hours to obtain the aminated titanium dioxide composite material. 2) The aminated titanium dioxide composite material was added to anhydrous ethanol, dispersed evenly, and then 1,3,5-trialdehyde phloroglucinol was added. Acetic acid was added dropwise, and the mixture was heated under reflux for 4-6 hours to obtain the pretreated titanium dioxide composite material. In-situ COF coating layer formed on S4 pretreated titanium dioxide composite material 1,3,5-trialdehyde phloroglucinol and 4,4'-diaminodiphenyl ether are dissolved in a mixed solvent composed of 1,4-dioxane, mesitylene and acetic acid to obtain a reaction solution. The pretreated titanium dioxide composite material is then immersed in the reaction solution and reacted for 72-75 hours to obtain a fluoride-modified TiO2 / COF photocatalyst.

2. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 1, characterized in that, In S1, the titanium dioxide sol is prepared using the following specific method: Add tetrabutyl titanate to anhydrous ethanol while stirring continuously at 150-200 rpm, then add glacial acetic acid and stir for 15-30 min to obtain a tetrabutyl titanate ethanol solution. Subsequently, mix deionized water and anhydrous ethanol, and add concentrated nitric acid dropwise to adjust the pH value to 2-3 to obtain a mixed solution. Add the mixed solution to the tetrabutyl titanate ethanol solution while stirring at 800-1000 rpm and continue stirring for 1-2 h.

3. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 2, characterized in that, In the tetrabutyl titanate ethanol solution, the volume ratio of tetrabutyl titanate, anhydrous ethanol, and glacial acetic acid is (5-10):(50-80):(2-3). In the mixture, the volume ratio of deionized water to anhydrous ethanol is (1-2):(10-15). The volume ratio of the mixture to the tetrabutyl titanate ethanol solution is (11-17):(57-93).

4. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 1, characterized in that, In S1, the calcination temperature is 450-500℃ and the calcination time is 1-2 hours.

5. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 1, characterized in that, In S2, the ratio of tetrabutyl titanate, concentrated nitric acid, deionized water, and ammonium fluoride in the precursor solution is (2-3) mL: (12-16) mL: (24-28) mL: (40-60) mg; The ratio of the pretreated titanium dioxide nanofibers to the precursor solution is (2-3) g: (42-70) mL; The reaction is carried out at a temperature of 150-160℃; The calcination is carried out at a temperature of 350-370℃ for 1-2 hours.

6. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 1, characterized in that, In S3-1), the ratio of the titanium dioxide composite material, anhydrous toluene, and 3-aminopropyltriethoxysilane is (2-3) g: (150-200) mL: (2-5) mL; The heating reflux reaction is carried out at a temperature of 110-115℃.

7. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 1, characterized in that, In S3-2), the ratio of the aminated titanium dioxide composite material, anhydrous ethanol, 1,3,5-trialdehyde phloroglucinol, and acetic acid is (1.5-2.0) g : (80-120) mL : (0.05-0.10) g : (0.1-0.2) mL; The acetic acid has a concentration of 6-8 mol / L; The heating reflux temperature is 80-85℃.

8. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 1, characterized in that, In S4, the ratio of 1,3,5-trialdehyde phloroglucinol, 4,4'-diaminodiphenyl ether, 1,4-dioxane, mesitylene, and acetic acid in the reaction solution is (0.63-0.72) g : (0.82-1.03) g : (15-25) mL : (15-25) mL : (0.3-0.5) mL; The acetic acid has a concentration of 6-8 mol / L.

9. The method for preparing a fluoride ion modified TiO2 / COF photocatalyst according to claim 1, characterized in that, In S4, the ratio of the pretreated titanium dioxide composite material to the reaction solution is (0.1-0.2) g : (30-50) mL; The reaction is carried out at a temperature of 120-130℃.

10. A fluoride ion modified TiO2 / COF photocatalyst, characterized in that, It is prepared by the method described in any one of claims 1-9.

Citation Information

Patent Citations

  • A mercaptopropionic acid-linked titanium dioxide covalent organic framework composite material, its preparation method and application

    CN114011467B